Optimization of a Pelton impeller geometry for particulate flow using numerical simulation. (2022) - Hidalgo, V.; Barragán, G.; Parra, C.; Cando, E.; Simbaña, S.; Velasco, M.; Erazo, J.; Mena, S.; Gonzáles-Palua, I.; Pérez-Sánchez, M.; Puga, D.
Abstract: The aim of this work is to develop a methodology for Pelton turbines performance improvement using reverse engineering, parametric design and CFD analysis. The methodology was applied on a real turbine from the company ELEPCO S.A. Initial geometry was obtained using resin and plaster mold, 3D scanning was applied to acquire a point cloud. The parametric CAD model was obtained by using Python along with parametric design tools from Autodesk Inventor. The optimization of the model was achieved by varying the entry and exit angles of the bucket. Numerical simulation was executed using ANSYS CFX with k-ω SST turbulence model.